Kees Van Gelder : de keeshond hapt. - Labro, Herman; van Gelder, Kees; evenandyet gallery, Leuven (Leuven : Biënnale Leuven, 2001)
Armleder, John M. ; Bragigand, Franck ; Fleury, Sylvie ; Fridfinnsson, Hreinn ; de Gruyter, Voebe ; Gudmundsson, Sigurdur ; Janssen, Twan ; Kloosterboer, Klaas ; Kroneman, Jaap ; Mosset, Olivier ; Marclay, Christian ; Peeters, Henk ; Ruggirello, Jean-Claude ; van der Stokker, Lily ; Temin, Kathy ; Vanderheyden, JCJ ; van Warmerdam, Marijke
Nederlands
De keeshond hapt, evenandyet gallery Leuven, Biënnale Leuven, 26.04 - 24.06.2001
boek